Late onset Krabbe's leukodystrophy: a report of four cases. Issue 4 (April 1991) - Phelps, M; Aicardi, J; Vanier, M T
Abstract : Four cases of late-onset Krabbe's leukodystrophy had varying clinical features. One sibling became wheelchair-bound while another leads an active working life. The computed tomography (CT) scan of a third patient showed occipital demyelination with contrast enhancement identical to that seen in an adrenoleucodystrophy. The fourth was the only patient with peripheral neuropathy. All patients had enzyme activity comparable to the classic infantile-onset form.